Margins o Difference: Constructing Critical Political Psychology - Nesbitt-Larking, Paul (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article sets out elements of discourse and rhetorical analysis in social psychology, followed by an elaboration of three key contributions of these approaches to critical political psychology. The first contribution urges researchers to pay attention to both their own and others’ ideological orientations. The second contribution addresses the artificial dualism of individual and society and how to transcend such oppositions. The third contribution is toward cross-cultural political psychology and the possibilities of political psychology beyond the framework of possessive individualism.